Macrophages and Their Organ Locations Shape Each Other in Development and Homeostasis – A Drosophila Perspective - Mase, Anjeli; Augsburger, Jordan; Brückner, Katja (Frontiers in Cell and Developmental Biology, 2021)
Across the animal kingdom, macrophages are known for their functions in innate immunity, but they also play key roles in development and homeostasis. Recent insights from single cell profiling and other approaches in the invertebrate model organism Drosophila melanogaster reveal substantial diversity among Drosophila macrophages (plasmatocytes). Together with vertebrate studies that show genuine expression signatures of macrophages based on their organ microenvironments, it is expected that Drosophila macrophage functional diversity is shaped by their anatomical locations and systemic conditions. In vivo evidence for diverse macrophage functions has already been well established by Drosophila genetics: Drosophila macrophages play key roles in various aspects of development and organogenesis, including embryogenesis and development of the nervous, digestive, and reproductive systems. Macrophages further maintain homeostasis in various organ systems and promote regeneration following organ damage and injury. The interdependence and interplay of tissues and their local macrophage populations in Drosophila have implications for understanding principles of organ development and homeostasis in a wide range of species.